Study and analysis of the correlation between lumbar spondylolisthesis and Modic changes - Li, Guang-qing; Kang, Xiao; Li, Wei; Pei, Shi-shen (Frontiers in Surgery, 2024)
Background This study aimed to explore the risk factors of Modic changes in lumbar spondylolisthesis. Methods The distribution of Modic changes in different types of lumbar spondylolisthesis, degree of spondylolisthesis, and degree of intervertebral disc degeneration in patients with lumbar spondylolisthesis was observed and analyzed. Statistical analysis was conducted to assess whether intervertebral disc degeneration, local mechanical changes, etc. affect the occurrence of Modic changes. The risk factors of Modic changes in lumbar spondylolisthesis were further illustrated. Results The age in the lumbar spondylolisthesis with Modic changes group was younger than that in the lumbar spondylolisthesis without Modic changes group, and the bone mineral density was better in the lumbar spondylolisthesis with Modic changes group than that in the lumbar spondylolisthesis without Modic changes group, P < 0.05. The two groups statistically differed in intervertebral disc height (IDH) and disc angle on magnetic resonance imaging (MRI). In the classification of Modic changes, the incidence of type II was the highest. The incidence of Modic changes is higher in isthmic spondylolisthesis than in degenerative spondylolisthesis. With the aggravation of lumbar spondylolisthesis and intervertebral disc degeneration, the incidence of Modic changes gradually increased. Modic changes are most commonly seen in both the upper and lower endplates. Logistic regression analysis showed that the occurrence of Modic changes in lumbar spondylolisthesis was significantly correlated with IDH, disc angle on MRI, type of spondylolisthesis, degree of spondylolisthesis, and degree of intervertebral disc degeneration, P < 0.05. Conclusions The occurrence of Modic changes is related to the type of spondylolisthesis, the degree of spondylolisthesis, the degree of disc degeneration, the decrease of intervertebral disc height, and local stress angulation.